PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN PT. BANK MEGA Tbk. CABANG PEKANBARU - Degustia, Frilla (JURNAL PLANS, 2017)
The objectives of this research are to analyze and investigate the compensation and motivation on employees performance at PT. Bank Mega Tbk. Pekanbaru Branch with overall test and individual test. The research method used is descriftive and verificative and the population in this research are 37 employees. Data collected with field and library study by using observation, interview and questionnaires. Multiple Regression Analysis is used to determine relationship and influence of variable and in order to test the hypothesis, statistical analysis is used. The result of research shows that multiple correlation coefficient t (R) valued at 0,730 with probability (p) 0,05 and determination coefficient value (R2) is 53,3%. It means that 53,3% factor compensation and motivation toward employees performance at PT. Bank Mega Tbk.  Pekanbaru Branch. It indicated from the value of F obs is large than F table at the level of α = 5% (F obs = 19,393 > f table = 3,32). From the figures, in the hypothesis null is rejected meaning the compensation and motivation have been relationship an influence of significant toward employees performance at PT. Bank Mega Tbk.  Pekanbaru Branch. A partially (individual test) shows that the value of t obs the biggest on compensation variable, t obs =3,275 > t table = 1,687 with a partial determination coefficient value (r2) = 49%. This result indicates that the compensation variable has most dominant relationship and influence on employees performance at  PT. Bank Mega Tbk.  Pekanbaru Branch. Key word : Compensation, Motivation and Employees Performance.